PP.41.14: ENDOTHELIAL FUNCTION IN ACUTE CORONARY SYNDROME. (June 2015) - Ramirez, M.; Maiorana, C.; Brito, S.; Lares, M.
Abstract : Objective: To evaluate the effect of omega - 3 fatty acids on endothelial function in acute coronary syndrome (ACS). Design and method: prospective study, open simplex, randomized 1:1, with a sample of 32 ACS patients divided into 2 groups; Group I: 16 patients treated with omega-3 at a dose of 3 grams / day + Conventional Therapy (O3 + Tc) vs Group II: 16 patients treated with conventional therapy (Tc) for SCA for 30 days. It was performed at 12 hours of admission and at 30 days, Lipid profile, C-reactive protein (usCRP), Interleukin 6 (IL-6), nitric oxide (NO), Endothelin 1 (ET-1) and Peptide Brain Natriuretic (NT pro BNP). Results: During 4 weeks of follow-up, the use of 3 grams / day of omega-3, added to conventional therapy in acute coronary syndrome showed a significant reduction of plasma NTproBNP (p = 0.036), IL-6 (p = 0.021) and triglycerides(p = 0.033). Conclusions: Three grams per day of omega-3 contributes to reduced plasma concentrations of triglycerides, NTproBNP and proinflammatory cytokines (interleukin-6) in patients with acute coronary syndrome.